158 Designing an online mentoring platform for clinical research coordinators: A structured approach - Alexandria Carey; Jennifer Moses; E. Mendy Dunn; Joyce Goodman (Journal of Clinical and Translational Science)
Objectives/Goals: Developing an online platform for the clinical research coordinator (CRC) mentoring program aimed to create an accessible space for professional development and peer support using Microsoft Teams. The platform fosters communication, community, and connection to share best practices and resources, enhancing competencies and growth within the CRC research learning community. Methods/Study Population: The CRC group mentoring program was developed using the ADDIE model. In the analysis phase, CRC needs were assessed to identify gaps in professional development, leading to the choice of Microsoft Teams for its effective communication and resource-sharing capabilities. The Design phase established objectives and content outlines for mentors and mentees. During development, training materials and interactive activities were created. Implementation involved onboarding participants and facilitating scheduled sessions. Finally, the Evaluation phase employed the Kirkpatrick model to assess program effectiveness: Level 1 gathered participant feedback, Level 2 measured knowledge gains, Level 3 tracked skill application, and Level 4 evaluated overall CRC performance and professional development impact. Results/Anticipated Results: Building and maintaining a learning community in Microsoft Teams with 16 mentors and 34 mentees across two health locations offers benefits and challenges. Benefits include the structured organization that facilitates collaboration, resource sharing, and real-time communication, regardless of location. Specific channels can focus discussions and virtual meeting scheduling streamlines coordination. Teams allow easy access to training materials and assessments. Challenges include maintaining engagement and fostering community. Asynchronous communication may lead to uneven participation, while digital literacy levels can hinder involvement. Sustaining meaningful interactions requires intentional facilitation and consistent encouragement to keep discussions dynamic and supportive. Discussion/Significance of Impact: The online Microsoft Teams mentoring platform boosts professional development, enhances community, and provides a vital space for resource sharing and discussion, thereby improving CRC competencies. Despite challenges like digital literacy and asynchronous communication, effective facilitation is crucial for empowering future leaders.